1999
DOI: 10.1038/sj.bjc.6690120
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerase IIα and -β expression in human ovarian cancer

Abstract: To study DNA topoisomerase IIα (Topo-IIα) and -β expression and regulation in human ovarian cancer, 15 ovarian tumour samples were investigated. To compare different levels of expression, the samples were screened for topo IIα and -β mRNA with Northern blotting and a quantitative reverse transcriptase polymerase chain reaction (RT-PCR) assay for Topo-IIα mRNA. Additionally, protein levels were determined with Western blotting and topoisomerase II activity levels with the decatenation assay. The results obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…We were thus able to evaluate gene expression in a large clinicopathologically characterized ovarian cancer cohort at the transcriptional and translational levels retrospectively without the requirement of special processing or preservation of specimens, as opposed to earlier studies on Top IIa in ovarian cancer surgical specimens, which required frozen tissue samples for the determination of Top IIa protein and RNA expression. 13,14,[26][27][28] We employed a new technique for RNA extraction from FFPE tissues, which is based on magnetic beads separation of nucleic acids, and used the sensitive real-time qRT-PCR method with specific TaqMan primer/probe to assess the transcriptional level of the Top IIa gene. Using this new technique, we showed that the determination of mRNA expression helps to identify aggressive tumors (high grade and high stage), and was linked to the mitotic activity of the tumor cells, yet does not add prognostic information compared with the evaluation of Top IIa protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…We were thus able to evaluate gene expression in a large clinicopathologically characterized ovarian cancer cohort at the transcriptional and translational levels retrospectively without the requirement of special processing or preservation of specimens, as opposed to earlier studies on Top IIa in ovarian cancer surgical specimens, which required frozen tissue samples for the determination of Top IIa protein and RNA expression. 13,14,[26][27][28] We employed a new technique for RNA extraction from FFPE tissues, which is based on magnetic beads separation of nucleic acids, and used the sensitive real-time qRT-PCR method with specific TaqMan primer/probe to assess the transcriptional level of the Top IIa gene. Using this new technique, we showed that the determination of mRNA expression helps to identify aggressive tumors (high grade and high stage), and was linked to the mitotic activity of the tumor cells, yet does not add prognostic information compared with the evaluation of Top IIa protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several observations have recently suggested that Topoisomerase IIa (TOPO-IIa), one of the two isoforms an enzyme playing a relevant role in DNA replication, repair, and transcription (Chung et al, 1989), is involved in critical steps of tumour cell proliferation and chemoresistance (Wang, 2002). Strong TOPO-IIa expression or enzymatic activity have been documented in ovarian carcinoma compared to the hardly detectable levels in benign ovarian tumours, ovarian inclusion cysts, and normal surface epithelium (van der Zee et al, 1991;Cornarotti et al, 1996;Withoff et al, 1999;Chekerov et al, 2006). The frequency of TOPO-IIa overexpression in ovarian cancer has been reported to range between 30 and 70% (van der Zee et al, 1994;Gotlieb et al, 2001;Koshiyama et al, 2001), and a definite role of this enzyme as a marker of sensitivity not only to TOPO-IIa targeting agents, such as anthracyclines and etoposide, but also to platinum agents in vitro and in vivo has been documented (Kikuchi et al, 1997;Naniwa et al, 2007).…”
mentioning
confidence: 99%
“…For instance, enhanced sensitivity to antiTopoII drugs was observed after adenovirus-mediated TopoIIa gene transfer in a human breast cancer cell line (Zhou et al, 2001). There is a marked heterogeneity of TopoIIa expression within different breast cancers (Sandri et al, 1996), various tissues (Turley et al, 1997;Withoff et al, 1999) and cell lines (Mo et al, 1998), which is responsible for the wide variety of anti-TopoII drug sensitivity. TopoIIa expression is linked to cell growth and is cellcycle regulated (reviewed in Isaacs et al, 1998;Nitiss, 1998).…”
mentioning
confidence: 99%